Cowpea (Vigna unguiculata): Genetics, genomics and breeding - Boukar, O.; Belko, N.; Chamarthi, S.; Togola, A.; Batieno, J.; Owusu, E.; Haruna, M.; Diallo, S.; Umar, M.L.; Olufajo, O.; Fatokun, C.A. (Wiley, 2019)
Cowpea, Vigna unguiculata (L.), is an important grain legume grown in the tropics where it constitutes a valuable source of protein in the diets of millions of people. Some abiotic and biotic stresses adversely affect its productivity. A review of the genetics, genomics and breeding of cowpea is presented in this article. Cowpea breeding programmes have studied intensively qualitative and quantitative genetics of the crop to better enhance its improvement. A number of initiatives including Tropical Legumes projects have contributed to the development of cowpea genomic resources. Recent progress in the development of consensus genetic map containing 37,372 SNPs mapped to 3,280 bins will strengthen cowpea trait discovery pipeline. Several informative markers associated with quantitative trait loci (QTL) related to desirable attributes of cowpea were generated. Cowpea genetic improvement activities aim at the development of drought tolerant, phosphorus use efficient, bacterial blight and virus resistant lines through exploiting available genetic resources as well as deployment of modern breeding tools that will enhance genetic gain when grown by sub‐Saharan Africa farmers.